Macht und Gewalt im Widerstreit - Meyer, Katrin (Schwabe reflexe, 2016)
This volume reconstructs Arendt's understanding of power and violence clearly and in detail. The author discusses the implications of Arendt's conception of power and violence for a political theory of democratic practice.